2020
DOI: 10.1080/1828051x.2020.1786739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium deficiency on testis development and autophagy in chicks

Abstract: To investigate the effects of Selenium (Se) deficiency on testis development and autophagy in chicks. 20 1-day old cocks were randomly divided into two groups, named the control check (CK) group [a basic diet (containing 0.333 mg Se/kg) was fed] and the Se-deficiency (Low Se) group [a selenium deficiency diet (containing 0.033 mg Se/kg) was supplied]. After 30 days, the body and testicle weights of the chicks were measured, and the organ coefficient was calculated. While haematoxylin-eosin staining, enzyme-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Furthermore, Se is a component of at least 25 selenoproteins and an important co-factor in the antioxidant enzyme system. Se consumption has an impact on nutrition utilization, productivity, antioxidative mechanisms, reproductive function, hormone metabolism, and immune system responses in productive animals [ 6 , 7 , 8 ]. In a study by [ 9 ], it was found that the yellowtail kingfish ( Seriola lalandi ) fed a diet without Se supplementation showed necrotic myopathy in fish muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Se is a component of at least 25 selenoproteins and an important co-factor in the antioxidant enzyme system. Se consumption has an impact on nutrition utilization, productivity, antioxidative mechanisms, reproductive function, hormone metabolism, and immune system responses in productive animals [ 6 , 7 , 8 ]. In a study by [ 9 ], it was found that the yellowtail kingfish ( Seriola lalandi ) fed a diet without Se supplementation showed necrotic myopathy in fish muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Se is an integral component of at least 25 selenopro-teins and serving as an essential co-factor in the antioxidant enzyme system. The intake of Se in productive animals affects nutrient utilization, productive performance, antioxidative mechanism, reproductive function, hormone metabolism and responses of the immune system [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue explants were incubated at 37 °C in an atmosphere containing 95% air and 5% CO 2 . Selenium (Sigma-Aldrich) doses (1, 5, and 10 μg/100 mg tissue) were chosen according to studies by Behne et al ( 1996 ), Shi et al ( 2017 ), and Li et al ( 2020 ). Selenium was dissolved in dimethyl sulfate (DMSO).…”
Section: Methodsmentioning
confidence: 99%